PENGEMBANGAN DESAIN SENI KERAJINAN TATAH SUNGGING KULIT PUCUNG IMOGIRI BANTUL YOGYAKARTA - Aruman Aruman; Toyyibah Kusumawati (Institut Seni Indonesia Yogyakarta, 2017)
One of the central handicraft center of leather sungging in Yogyakarta is in the area of Pucung Karangasem Wukirsari Imogiri Bantul. Dusun pucung karangasem, is a village known for its leather craft. One of the famous handicraft products in the world is wayang kulit. But not only that, besides wayang, other handicraft products coming from leather can be lampshade, bookmark, tissue box, candle holder, fan, keychain, wall decoration, and others.In running the craft business, the craftsmen joined in groups, including the group